Oral Presentations 1981
DOI: 10.1055/s-0038-1652130
|View full text |Cite
|
Sign up to set email alerts
|

Adherent Mononuclear Cells And Activated Protein C (APC)

Abstract: Addition of bovine APC to dilute whole blood or euglobulin assays of fibrinolytic activity produces little effect on rates of clot lysis. However, addition of APC to undiluted non anti coagulated or to 3.2% citrated whole blood followed by 125I-fibrinogen and thrombin produces clots which release fibrin degradation products and lyse within 24 hours. Ordinarily clotted non-anticoagulated whole blood does not lyse.Addition of increasing amounts of APC from 12-100ug/ml increases the rate of whole blood clot lysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A subsequent study (1985) demonstrated that infusion of thrombin with endotoxin also protected the dogs, suggesting that this was the case [59]. This work was closely followed by studies demonstrating the prophylactic [9] and therapeutic [10,60] efficacy of plasma APC and rhAPC in treatment of baboons infused with LD 100 E. coli (1986–87).…”
Section: Preclinical Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…A subsequent study (1985) demonstrated that infusion of thrombin with endotoxin also protected the dogs, suggesting that this was the case [59]. This work was closely followed by studies demonstrating the prophylactic [9] and therapeutic [10,60] efficacy of plasma APC and rhAPC in treatment of baboons infused with LD 100 E. coli (1986–87).…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…In spite of our increasing understanding of the biochemistry [1,2] and physiology [3–8] of the protein C network and the anticoagulant and anti‐inflammatory [9,10] functions of activated protein C in primate models of sepsis, our knowledge of how it protects patients with severe sepsis remains more limited. What is not fully recognized, however, is our equally limited knowledge of the various pathophysiologic processes that constitute the severe sepsis syndrome on which activated protein C has been shown to act.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phospholipid and Ca2' accelerate the inactivation of Factor Va and VIIIa by protein Ca (4)(5)(6)(7)(8)(9). Protein Ca also generates fibrinolytic activity in blood both in vitro (10)(11)(12) and in vivo (13)(14). The in vivo effects are mediated, at least in part, by increased levels of circulating plasminogen activator (14).…”
mentioning
confidence: 99%